Syphilis in presentation with overlapping phases: how to lead? - Bernardes Filho, Fred; Santos, Maria Victória P.Q.; Cariello, Lorena B.A.; Ferrari, Veronica V.B.; Serra, Amanda C.; Alves, Andreia O.; Doni, Shimelis N.; Nery, José A.C. (Brazilian Journal of Sexually Transmitted Diseases, 2012)
Syphilis is an infectious disease of high prevalence, especially in underdeveloped countries, and is often called the “great imitator” due to its versatile and varied disease presentations. The disease’s division into stages is only didactic and has importance in the therapeutic management, however syphilis should be managed as a dynamic disease, due to its possibility of overlapping stages. The authors report two cases in which there is concomitance of primary and secondary syphilis and emphasize the importance of patient global assessment in STD.